Amylolytic Isoenzymes of Thermoactinomyces vulgaris - Allen, Martin J. (1972)
Thermoactinomyces vulgaris strain 5 produced two electrophoretically different α-amylases. Precipitation with ammonium sulfate and acetone did not alter the electrophoretic mobilities of either amylase isoenzyme. Patterns of the hydrolysis products of amylose by the two amylase isoenzymes were essentially identical.